Trade and Child Labour in SAARC Countries - Bilal, Tariq; Rossazana Ab-Rahim, Ab-Rahim (2021)
A review of past studies shows that the studies confine their analysis of trade and child labour in the setting of the trading of homogeneous goods. Hence, the presence study aims to assess the relationship of trade and child labour in South Asian Association for Regional Cooperation (SAARC) countries by incorporating the role of selection of variety or product heterogeneity in child labour demand.In the context of trade in homogeneous and heterogeneous goods, the trade-induced effectsare the selection, scale,and technique effects. The panel data analysis is employed to investigate the nexus between trade and child labour over the study period of 1999 to 2019. The results imply that the opening of trade alone will not reduce child labour if itis not accompanied by supportive measures, namely the trade-related effectof child labour, theeffectof scale and technique. Therefore, this study suggests that trade liberalization through trade-induced effectwould hamper the child labour presence in the emerging markets.